2019
DOI: 10.1111/ecc.13164
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference for oral chemotherapy in the treatment of metastatic breast and lung cancer

Abstract: Objectives Although new therapies against metastatic cancer have been developed in recent decades, chemotherapy is still an important treatment option. Prolonged treatment and side‐effects are often discouraging for patients, and in many cases, therapy is only palliative, not curative. This study explores patient preference for oral or intravenous (IV) chemotherapy in the treatment of metastatic breast or lung cancer. Methods It is a descriptive, open label, multicentre, nation‐wide study, in which a 16‐item q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Recently, Ciruelos and colleagues (2019) have confirmed that a majority of patients (77%) with breast or lung cancer preferred oral therapy due to less disruption of daily life, no trouble in swallowing oral therapy, and no issues with missing doses. This patient population had already received IV therapy and at least two cycles of oral chemotherapy, with 56.3% reporting problems related to drug infusion with IV therapy, 61.7% expressing concerns about nurses failing to find suitable veins, and 63.1% reporting dissatisfaction with hospital waiting times ( Ciruelos et al, 2019 ). In light of these data, an increasing number of oral chemotherapeutics are under development and are expected to become available soon ( Jibodh et al, 2013 ; Stuurman et al, 2013 ).…”
Section: Patient Preference For Oral Therapiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Ciruelos and colleagues (2019) have confirmed that a majority of patients (77%) with breast or lung cancer preferred oral therapy due to less disruption of daily life, no trouble in swallowing oral therapy, and no issues with missing doses. This patient population had already received IV therapy and at least two cycles of oral chemotherapy, with 56.3% reporting problems related to drug infusion with IV therapy, 61.7% expressing concerns about nurses failing to find suitable veins, and 63.1% reporting dissatisfaction with hospital waiting times ( Ciruelos et al, 2019 ). In light of these data, an increasing number of oral chemotherapeutics are under development and are expected to become available soon ( Jibodh et al, 2013 ; Stuurman et al, 2013 ).…”
Section: Patient Preference For Oral Therapiesmentioning
confidence: 98%
“…Several surveys and studies have reported an increased acceptance for oral drugs among patients and health-care professionals ( Ciruelos et al, 2019 ; Eek et al, 2016 ; Navarro et al, 2002 ; Schott et al, 2011 ). An analysis of previous studies indicates that most patients who have experienced oral agents do not favor IV chemotherapy and report a clear preference for oral chemotherapy for breast cancer treatment ( Eek et al, 2016 ).…”
Section: Patient Preference For Oral Therapiesmentioning
confidence: 99%
“…[8][9][10] Inconvenience associated with treatments given as IV infusions or SC injections has also been identified as a barrier to adherence in other therapeutic areas, for which there are both injected and oral disease-modifying therapies available, with higher adherence and satisfaction reported by patients receiving oral therapies. Oral therapy typically offers multiple convenience advantages such as less disruption of daily life 11 and reduction in stress and discomfort associated with injectable treatments. 12 A recently approved oral form of HMA, a combination of decitabine with cedazuridine, 13 may be able to alleviate some of the challenges experienced by MDS patients (and caregivers) who receive HMA therapy via infusions/injections.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with psoriasis, treatment attributes focusing on convenience and lifestyle compatibility, i.e., treatment location and route of administration, were considered to be more important than adverse effects [17]. Several studies for cancer treatments have found oral treatments to be preferred over intravenous administration across a range of cancer patient populations citing a variety of reasons, including greater flexibility, convenience, less stress, and better quality of life [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%